2021
DOI: 10.3390/cancers13133184
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Spatial Peptide Signatures for Neuroblastoma Risk Assessment by MALDI Mass Spectrometry Imaging

Abstract: Risk classification plays a crucial role in clinical management and therapy decisions in children with neuroblastoma. Risk assessment is currently based on patient criteria and molecular factors in single tumor biopsies at diagnosis. Growing evidence of extensive neuroblastoma intratumor heterogeneity drives the need for novel diagnostics to assess molecular profiles more comprehensively in spatial resolution to better predict risk for tumor progression and therapy resistance. We present a pilot study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…[56] Furthermore, spatial proteomics and/or transcriptomics of the coculture models could shed light onto the specific cell-cell interactions underlying NB invasion and metastasis. [57] The endothelialized NB models could also serve as a highthroughput platform to study antiangiogenic therapies that are being pursued as a method of starving tumors of their energy supply. [45,58] More in-depth functional and biological characterization of bioprinted tumor models were performed via examining metabolic activity, angiogenesis-associated cytokines, and gene expression profiles of the incorporated cells.…”
Section: Resultsmentioning
confidence: 99%
“…[56] Furthermore, spatial proteomics and/or transcriptomics of the coculture models could shed light onto the specific cell-cell interactions underlying NB invasion and metastasis. [57] The endothelialized NB models could also serve as a highthroughput platform to study antiangiogenic therapies that are being pursued as a method of starving tumors of their energy supply. [45,58] More in-depth functional and biological characterization of bioprinted tumor models were performed via examining metabolic activity, angiogenesis-associated cytokines, and gene expression profiles of the incorporated cells.…”
Section: Resultsmentioning
confidence: 99%
“…In malignant tumors, AHNAK lacks uniform expression and has different intracellular localizations depending on the tumor cell type [14] [15] [16]. AHNAK in neuroblastoma cell lines is described as a nuclear protein whose expression is significantly suppressed [17], whereas, in a study on melanoma, an immune response was observed mainly in the cytoplasm of normal cells, in contrast to the disappearance of expression in melanoma cells [18]. IRGPI is associated with the infiltration of multiple immune cells [19], which contributes to further revealing the role and interrelationship of immune cells in the immune microenvironment of bladder cancer, and as the risk value of IRGPI increases, the later the clinical stage of the patient, the progressive impairment of the main immune function of the body leading to tumor development and metastasis, etc., these differences in the level of infiltration of immune-related cells may indicate the risk value potential immune mechanisms, which could have significant clinical application by detecting relevant infiltrating immune cells in bladder cancer patients to distinguish high and low-risk groups or as immune targets.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 9 of our 10 tumor enriched peptide features matched within a 300 ppm window to peptide mass features that have been described as tumor specific in three other solid tumor MALDI imaging studies (Table 2). These studies compared vulvar squamous cell carcinomas to precursor lesions, head and neck cancer tumor epithelial regions with non-tumor tissue regions, and neuroblastoma cell rich tumor regions with surrounding non-tumor tissue [39][40][41] . MALDI imaging measures majorly the most abundant proteins 42 and thus it is likely that universal solid tumor protein markers can be found even across very different cancer types.…”
Section: Spatial Proteome Represents Tissue Morphologiesmentioning
confidence: 99%